ANALISIS FAKTOR KEPATUHAN IBU HAMIL DALAM KUNJUNGAN ANTENATAL CARE BERDASARKAN HEALTH BELIEF MODEL - GEBYAR HAFIT SUWANDARU, 131211133016 (2016)
Antenatal care is one of main preventif for pregnant woman to decrease complication on pregnantcy. Some of them may cause a seriously problem. The design of the study was descriptive analytic with cross-sectional approach. The population was pregnant woman who had gestational age more than 36 weeks. The 38 sample respondents were chosen by purposive sampling. The independent variables in this study were perceived susceptibility, perceived seriousness, perceived benefit, percieved barrier, and cues to action. The dependent variable was compliance visits on antenatal care. The data were collected by using questionnaire and analyzed by using chi square test with a degree of significance α < 0.05. The results showed a correlation between perceived susceptibility factor (p = 0.003), perceived seriousness (p = 0.000), perceived benefit (p = 0,000), and perceived barrier (p=0,011) with compliance visits of antenatal care on pregnant woman. The cues to action (p = 0.126) does not affect the pregnant women. Some factors in health belief model have a correlation with compliance visits of antenatal care on pregnant woman. To health care facilities are expected to direct more pregnant women to be obedient in antenatal care visit trough the approach of factors that may support and hinder compliance.